USE OF POWER TEACHING GAME TECHNIQUE (POW- TEGA) TO IMPROVE SPEAKING SKILL OF JUNIOR HIGH SCHOOL STUDENTS - Armansyah, Armansyah (Universitas Borneo Tarakan, 2019)
The aim of this research was to find out whether power teaching game technique (Pow-Tega) could improve the students’ speaking skill or not. The sample was selected using purposive sampling from the population, they were thirty-two students from class VII-5. Pre-Experimental design was used in this research. To find whether the power teaching game technique (Pow-Tega) could improve students’ speaking skill, the oral test was used to collect the data. The data were analyzed by using paired sample t-test. The result showed that there was an improvement in students’ speaking skill after being taught by using power teaching game technique (Pow-Tega). It could be seen from the increase of students’ mean score from pre-test to posttest, 42.13 to 59.38. Moreover, based on the result of paired sample t-test, t-result was -9.018, t-table was -2.040 (p 0.05) and the significant value was 0,000 (p 0.05). The result showed that the students who were taught by using power teaching game technique (Pow-Tega) had a better improvement in their speaking skill. In other words, power teaching game technique (Pow-Tega) is a good way to be used by the teachers as a teaching technique especially in improving students’ speaking skill.